LISTENING BEFORE SPEAKING: RETHINKING SKILLS DEVELOPMENT IN LANGUAGE TEACHING (SCIENCE TIME JOURNAL, 2026)
Listening and speaking are highly related skills of learning a language with speaking production being the key activity in most traditional language teaching methods but listening input has not been given adequate attention. This disproportion can impair the process of learning the oral language of fluent and correct language. This paper will explore the purpose of listening as a precursor to the development of speaking skills and makes the case that it is impossible to develop competence in speaking effectively without engaging in systematic listening exercises. The interpretation of the research design was a mixed method because data was gathered by classroom observation, learner questionnaires, and assessment of speaking performance. The results show that learners who take part in organized listening activities show more gains in fluency, pronunciation, and communicative confidence. The paper concludes that reconsidering the way skills are developed and focusing on listening before speaking can be an effective way to improve oral proficiency and offers pedagogical consequences to the practice of language teaching.